Identifikasi dan Evaluasi Pengaruh Ventilasi Alami pada Ruang Kelas Terhadap Fenomena Sick Building Syndrome - Latifah, Latifah; Widiastuti, Ratih (Jurnal Sipil dan Arsitektur, 2023)
Natural ventilation is closely related to the indoor air quality and will affect the occupant activities. The unhealthy air conditioning will create discomfort for the occupants. One of the phenomena that is caused by indoor air quality is Sick Building Syndrome (SBS). Bad air circulation systems in the classroom can lead to Sick Building Syndrome (SBS) among students. This study was conducted to identify and evaluate the influence of natural ventilation in the classroom on the Sick Building Syndrome phenomenon. The object of the study was classrooms in the Department of Architecture, Faculty of Engineering, Diponegoro University. Data of temperature, relative humidity, and air velocity were collected to identify the indoor air quality of the classrooms. Based on the analysis, either with closed or open natural ventilation, the indoor air quality inside the classroom still did not meet the requirement of healthy air. Therefore, further actions such as improving the quality of natural ventilation are needed.